The Impact of Changes in InFeed Rate on Surface Integrity after Chrome Plate Grinding by Silicon Carbide - Marek, Martin; Novák, Martin; Šramhauser, Karel (Manufacturing Technology Journal, 2019)
Grinding is a significant and very commonly used technology, allowing for important gains in surface integrity. The surface integrity quality after grinding is one of the most important parameters, which is prescribed on the production drawing. Chrome plating as protection against corrosion, erosion, abrasion and as a material for the overhaul of worn-out parts is used. This paper discusses the change of cutting conditions when samples were ground. The surface of all samples was preserved with galvanically applied chrome. The values show which grade of surface roughness is attained when selecting different cutting conditions. The results of surface integrity after grinding were evaluated depending on the comparison of the parameters of roughness. The input parameters of cutting conditions were chosen based on the experience, which was implemented.
Keywords: grinding; hard chrome plate; surface integrity; cutting conditions